Field-Based Radiographic Imaging of Marine Megafauna: Marine Iguanas (Amblyrhynchus cristatus) as a Case Study - Lewbart, Gregory A.; Cohen, Eli B.; Hirschfeld, Maximilian; Muñoz-Pérez, Juan Pablo; García, Juan; Fu, Andy; Chen, Emile P.; Lohmann, Kenneth J. (Frontiers in Marine Science, 2018)
Effective conservation of marine megafauna requires a thorough understanding of the ecology, physiology, population dynamics, and health of vulnerable species. Assessing the health of large, mobile marine animals poses particular challenges, in part because the subjects are difficult to capture and restrain, and in part because standard laboratory and diagnostic tools are difficult to apply in a field setting. Radiography is a critically important diagnostic tool used routinely by veterinarians, but it has seldom been possible to image live marine vertebrates in the field. As a first step toward assessing the feasibility of incorporating radiography into studies of vulnerable species in remote locations, we used portable radiographic equipment to acquire the first digital internal images of living marine iguanas, Amblyrhynchus cristatus, an iconic lizard endemic only to the Galápagos Islands of Ecuador. The radiographic machinery was powered by batteries and performed well on a rocky beach environment of an uninhabited island, despite high heat and humidity. The accuracy of radiographic measurements was validated by computing a snout-vent length (SVL) using bone dimensions and comparing this to standard measurements of SVL made externally with a tape measure. These results demonstrate the feasibility of using radiography to study animals in remote sites, a technique that may prove useful for a variety of physiological, ecological, and biomechanical studies in which reliable measurements of skeletal and soft-tissue dimensions must be acquired under challenging field conditions. Refinements are discussed that will help the technology reach its full potential in field studies.